2016
DOI: 10.1186/s40064-016-2579-5
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-like psychosis and gitelman syndrome: a case report and literature review

Abstract: IntroductionGitelman syndrome(GS) is a rare inherited tubular disorder which is characterized by hypokalemia, metabolic alkalosis, hypomagnesemia, and hypocalciuria. Here, we report a case of schizophrenia-like psychosis concomitant with GS and related literatures are reviewed.Case descriptionAn 18-year-old male patient with 1-week history of auditory hallucinations, sense of insecurity, delusions of reference and feelings of being followed and controlled by others unknown, insomnia was admitted to Psychiatry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Because of similar clinical manifestations, GS is considered a subtype of Bartter Syndrome having hypomagnesemia and hypocalciuria. A few years ago, the molecular basis of GS was revealed by Simon et al They first demonstrated a linkage of GS to the locals encoding the renal NCC, an integral membrane protein consisting of 1030 amino acids with 12 transmembrane and intercellular N and C-terminal domains [8,25]. Thereafter, a series of studies identified the human SLC12A3 gene, which encodes the NCC.…”
Section: Discussionmentioning
confidence: 99%
“…Because of similar clinical manifestations, GS is considered a subtype of Bartter Syndrome having hypomagnesemia and hypocalciuria. A few years ago, the molecular basis of GS was revealed by Simon et al They first demonstrated a linkage of GS to the locals encoding the renal NCC, an integral membrane protein consisting of 1030 amino acids with 12 transmembrane and intercellular N and C-terminal domains [8,25]. Thereafter, a series of studies identified the human SLC12A3 gene, which encodes the NCC.…”
Section: Discussionmentioning
confidence: 99%
“…These included 3 articles in China (sample size is 67, 47, 20 people); 1 article in Switzerland [ 5 ] (163 people), 1 in the UK [ 6 ] (36 people), and 1 in South Korea [ 7 ] (34 people). The remainders of the relevant research were mainly case reports reflecting the complications reported, such as combined Sjogren’s syndrome [ 8 ], combined pregnancy or pregnancy HELLP syndrome [ 9 ], primary hyperparathyroidism [ 10 ], complete growth hormone deficiency [ 11 ], schizophrenic changes [ 12 ], and Fanconi syndrome [ 13 ]. Hypokalaemia is a common significant feature among them.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search found a single case report of a patient with schizophrenia and Gitelman syndrome and a single case report of a patient with a purging eating disorder and Gitelman syndrome, demonstrating the rarity of these co‐occurrences (Pan, Mou, Li, Liu, & Hu, ; Lee, Lee, & Han, ). To our knowledge, this is the first reported case of a single patient with a co‐occurring eating disorder, psychosis, and Gitelman syndrome.…”
Section: Introductionmentioning
confidence: 99%